2020
DOI: 10.18502/ijm.v11i6.2226
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus in thalassemia patients with hepatitis C in Tehran, Iran

Abstract: Background and Objectives: HEV infection is predominantly spread via the fecal-oral route; however, due to the presence of HEV RNA in the serum of healthy blood donors, there is a possibility of the transmissibility of HEV infection through blood. Multi-transfused thalassemia patients are one of the high risk groups for blood borne viruses. In this study, we evaluated the prevalence of HEV antibodies and HEV-RNA in thalassemia patients with HCV infection. Materials and Methods: 120 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To detect the HEV genome, the HEV ORF2 genome sequence was amplified by RT-nested PCR with specific previous primers (20). The sequences of the outer primers were 5′ -GAG GCA GGC ACA ACT AAA GC-3′ and 5′ -AAG AAG GGG GGC ACA AG-3′, and The sequences of the inner primers were 5′ -GCA CCG GGT CGC TAT TTC-3′ and 5′ -TGA AGC TCA GCG ACA GTA GA-3′.…”
Section: Genomic Rna Preparation and Detection Of Hev Rna By Rt-neste...mentioning
confidence: 99%
“…To detect the HEV genome, the HEV ORF2 genome sequence was amplified by RT-nested PCR with specific previous primers (20). The sequences of the outer primers were 5′ -GAG GCA GGC ACA ACT AAA GC-3′ and 5′ -AAG AAG GGG GGC ACA AG-3′, and The sequences of the inner primers were 5′ -GCA CCG GGT CGC TAT TTC-3′ and 5′ -TGA AGC TCA GCG ACA GTA GA-3′.…”
Section: Genomic Rna Preparation and Detection Of Hev Rna By Rt-neste...mentioning
confidence: 99%
“…Twenty percent ( n = 8/40) of multiply transfused thalassemia patients were anti-HEV IgG positive compared with 11.0% ( n = 10/91) in blood donors[ 154 ]. In contrast, a study in Iran found anti-HEV antibodies in only 1.67% of patients with thalassemia, suggesting a low rate of TT-HEV in that country[ 155 ]. Results from these two studies in thalassemia patients were limited by the small sample size.…”
Section: Transfusion-transmitted Hepatitis Ementioning
confidence: 99%
“…Additionally, intriguing questions concerning the role of transfused blood as a potential carrier of these commensal-like viruses are still unanswered. These aspects raise concern over blood safety and vulnerability of frequently exposed individuals, such as immunocompromised and multi-transfused patients [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%